Retrospective Analysis of Culture Results of Cases with Acute Vulvovaginitis: University Experience - Türkçüoğlu, Ilgın; Engin Üstün, Yaprak; Üstün, Yusuf; Yetkin, Gülay (Gynecology Obstetrics & Reproductive Medicine, 2008)
OBJECTIVE: To analyse the results of the vaginal cultures and find out the prevalence of pathogens in patients with acute vulvovaginitis, retrospectively. STUDY DESIGN: Vaginal cultures results of patients with the diagnosis of acute vulvovaginitis were analyzed retrospectively between June 2005 and January 2006. RESULTS: Totally 241 patients were included in the study within 6 months time period. Mean age of patients was 30,63±6,87 changing between 19 and 57 years. While there was no pathogen detected in 18,3% (44/241) of vaginal cultures, various pathogens growed in 81,7% (197/241) of cultures. Normal vaginal flora was detected in 70,6% (139/197) of cultures with growth. The second most common pathogen was Candida subspecies with a rate of 14,2% (28/197). Other pathogens were Candida albicans, E.coli, Gardnerella vajinalis, Klebsiella pneumonia, Candida subspecies and Klebsiella, Candida albicans and Klebsiella, Candida albicans and Gardnerella vajinalis with a rate of %7,1 (14/197), %4,1 (8/197), %2 (4/197), %0,5 (1/197), %0,5 (1/197), %0,5 (1/197) and %0,5 (1/197) respectively. CONCLUSION: The most frequent pathogen detected in culture of patients with acute vulvovaginitis was candida subspecies in our clinic.